Knowledge Of Tuberculosis and Its Management Practices Amongst Postgraduate Medical Students in Pune City - Rahul R Bogam; Sunil M Sagare (Medsci Publications, 2011)
The study was aimed to assess the pre and post training knowledge of tuberculosis and its management amongst newly admitted postgraduate students in medical college and hospital. India accounts for nearly one fifth of global burden of tuberculosis. Every year approximately 1.8 million persons develop tuberculosis. Postgraduate students are many times the first contact of patients in teaching as well as secondary and tertiary care hospitals. Considering this fact, the current study was conducted to assess pre and post training knowledge about basic facts of tuberculosis and its management practices. All newly admitted postgraduate students attended RNTCP training and completed pretest and posttest questionnaires. Each completed questionnaire was assigned marking system. The data was analyzed using paired t test. Significant improvement in knowledge was found after RNTCP Training (Pretest mean marks: 10.25, posttest mean marks: 14.36, t=8.43, df=35, p=0). The education of postgraduate students on guidelines for detection and early management of TB is crucial for further improvement in national tuberculosis control strategies. RNTCP training should be a part of regular activity of all medical colleges and hospitals.